Method for Storing Digital Information and Storage Element: A Thermal Memory Cell - Dolinsek, Janez (Recent Patents on Materials Science, 2015)
A concept of thermal storage of digital information in a thermal memory cell as described in the patent “Method for storing digital information and storage element” (EP2207177) is presented, where a byte of digital information can be stored into the storage medium by pure thermal manipulation, in the absence of an electric or a magnetic field. Thermal inscription of information employs a specific temperature-time profile that involves continuous cooling and isothermal waiting (aging) time periods. The employed storage media were magnetically frustrated metallic solids. We succeeded to thermally write arbitrary ASCII characters into the Taylor-phase T-Al3(Mn,Fe) complex intermetallic compound and the Cu-Mn canonical spin glass.
Keywords: thermal memory cell